Belimumab and Rituximab in Systemic Lupus Erythematosus: A Tale of Two B Cell-Targeting Agents - Wise, Leanna M.; Stohl, William (Frontiers in Medicine, 2020)
Given the centrality of B cells to systemic lupus erythematosus (SLE), it stands to reason that a candidate therapeutic agent that targets B cells could be efficacious. Both rituximab, a monoclonal antibody (mAb) that binds to CD20 on the surface of B cells, and belimumab, a mAb that binds and neutralizes the B cell survival factor BAFF, have been extensively studied for the treatment of SLE. Despite the greater ability of rituximab to deplete B cells than that of belimumab, randomized controlled trials of rituximab in SLE failed to reach their primary clinical endpoints, whereas the primary clinical endpoints were reached in four independent phase-III clinical trials of belimumab in SLE. Accordingly, belimumab has been approved for treatment of SLE, whereas use of rituximab in SLE remains off-label. Nevertheless, several case series of rituximab have pointed to some utility for rituximab in treating SLE. In this review, we provide a concise summary of the factors that led to belimumab’s success in SLE as well an analysis of the elements that may have contributed to the lack of success seen in the rituximab randomized controlled trials in SLE.